Prevalence and influencing factors of self-medication during the COVID-19 pandemic in the Arab region: a multinational cross-sectional study - Aya Elsayed Abdelwahed; Mostafa Mahmod Abd-elkader; Amany Mahfouz; Mohammed Osama Abdelmawla; Marwa Kabeel; Amr Gabr Elkot; Mohamed Rabiea Hamad; Rahma Abd Elfattah Ibrahim; Marwa M. I. Ghallab; Collaborators group; Nouran Hamza (BMC, 2023)
Abstract Background The novel coronavirus pandemic (COVID-19) has begun with a wave of misinformation and fear of infection. This may have led people to self-medicate inappropriately. The World Health Organization describes self-medication (SM) as utilizing medicines to relieve symptoms or health conditions without consulting a physician. Inappropriate drug use is a burden on both health resources and patient health in the Arab region. This study aimed to detect the prevalence and influencing factors of self-medication among the general Arab population during the COVID-19 pandemic. Methods A multinational cross-sectional study was conducted among the general population of ten Arab countries from early August to late October 2021. Participants aged 18 years or older could join the study via social media platforms. A convenience sampling technique was used. A developed and validated web-based questionnaire was used to collect data on self-medication practice, associated influencing factors, information sources, commonly used medications, and commonly treated conditions. Descriptive, univariate, and multivariate regression analyses were applied using IBM SPSS v 26 and R v 4.0.0 software. Results A total of 8163 participants completed the questionnaire, and 518 participants were excluded from the analysis due to inconsistencies in their data. Almost two-thirds (62.7%) of participants reported practicing self-medication during the COVID-19 pandemic. At the country level, Egypt had the highest prevalence of self-medication practice (72.1%), while Palestine had the lowest prevalence (40.4%). The most commonly used drugs were analgesics, antipyretics, and vitamins (86, 65.1, and 57.1%, respectively), while antitussives and antibiotics scored 47.6 and 43.3%, respectively. Experience with similar health conditions (74.6%) and urgency of the problem (47.2%) were the most frequent factors that led to self-medication. Additionally, 38.2% of the self-medicated participants (SMPs) used drugs as prophylaxis against COVID-19. Pharmacist consultation was the most common source of information about self-medication (66.7%). Multivariate analysis showed that predictors of self-medication were older age (p = 0.008), presence of chronic illness (p = 0.015), and having monthly income or medical insurance that does not cover the treatment cost (p = 0.001, p < 0.001, respectively). Conclusion Self-medication is considered a common practice across the Arab population. It is necessary to regulate policies and raise awareness among the public about self-medication.